The role of osteopontin (OPN/SPP1) haplotypes in the susceptibility to Crohn's disease. - Jürgen Glas; Julia Seiderer; Corinna Bayrle; Martin Wetzke; Christoph Fries; Cornelia Tillack; Torsten Olszak; Florian Beigel; Christian Steib; Matthias Friedrich; Julia Diegelmann; Darina Czamara; et al. (PLoS ONE, 2011)
BACKGROUND: Osteopontin represents a multifunctional molecule playing a pivotal role in chronic inflammatory and autoimmune diseases. Its expression is increased in inflammatory bowel disease (IBD). The aim of our study was to analyze the association of osteopontin (OPN/SPP1) gene variants in a large cohort of IBD patients. METHODOLOGY/PRINCIPAL FINDINGS: Genomic DNA from 2819 Caucasian individuals (n = 841 patients with Crohn's disease (CD), n = 473 patients with ulcerative colitis (UC), and n = 1505 healthy unrelated controls) was analyzed for nine OPN SNPs (rs2728127, rs2853744, rs11730582, rs11739060, rs28357094, rs4754 = p.Asp80Asp, rs1126616 = p.Ala236Ala, rs1126772 and rs9138). Considering the important role of osteopontin in Th17-mediated diseases, we performed analysis for epistasis with IBD-associated IL23R variants and analyzed serum levels of the Th17 cytokine IL-22. For four OPN SNPs (rs4754, rs1126616, rs1126772 and rs9138), we observed significantly different distributions between male and female CD patients. rs4754 was protective in male CD patients (p = 0.0004, OR = 0.69). None of the other investigated OPN SNPs was associated with CD or UC susceptibility. However, several OPN haplotypes showed significant associations with CD susceptibility. The strongest association was found for a haplotype consisting of the 8 OPN SNPs rs2728127-rs2853744-rs11730582-rs11439060-rs28357094-rs112661-rs1126772-rs9138 (omnibus p-value = 2.07×10⁻⁸). Overall, the mean IL-22 secretion in the combined group of OPN minor allele carriers with CD was significantly lower than that of CD patients with OPN wildtype alleles (p = 3.66×10⁻⁵). There was evidence for weak epistasis between the OPN SNP rs28357094 with the IL23R SNP rs10489629 (p = 4.18×10⁻²) and between OPN SNP rs1126616 and IL23R SNP rs2201841 (p = 4.18×10⁻²) but none of these associations remained significant after Bonferroni correction. CONCLUSIONS/SIGNIFICANCE: Our study identified OPN haplotypes as modifiers of CD susceptibility, while the combined effects of certain OPN variants may modulate IL-22 secretion.